Berlin, die Stadt, die immer wird - Chiaramonte, Giovanni 1948-2023 (Schirmer/Mosel, 2009)
With his distinct southern touch, Italian photographer Giovanni Chiaramonte sheds an unusually balmy light on this much-photographed city. Casting a sensitive eye not only on its architecture, but also to empty lots and places not represented in official tourist guides, he discovers the hidden lines of fate and clandestine beauty of a city charged with history. The pictures were taken from 1984-2003.